Internalisasi Nilai-Nilai Pancasila dalam Mewujudkan Integrasi Nasional melalui Kajian Literatur Sistematis - Ni Putu Ayu Widiastiti; Dewa Bagus Sanjaya; I Nengah Suastika (Varied Knowledge Journal, 2026)
The strengthening phenomena of intolerance, social polarization, and information disruption in the digital era indicate serious challenges to national integration in Indonesia. This condition reflects that the internalization of Pancasila values in society, particularly among the younger generation, has not been optimal. This study aims to systematically examine the role of internalizing Pancasila values in realizing national integration through a Systematic Literature Review (SLR) approach. The research was conducted by analyzing 15 relevant scholarly articles obtained from various reputable databases through a structured selection process based on inclusion and exclusion criteria. The findings reveal that the internalization of Pancasila values contributes to fostering tolerance, strengthening social cohesion, and enhancing national awareness within a multicultural society. The process is effectively implemented through civic education, multicultural education practices, as well as strengthening the role of social environments and digital media as spaces for value internalization. In addition, contextual and adaptive approaches to contemporary developments are important factors in the successful implementation of Pancasila values. The implications of this study emphasize the importance of strengthening educational strategies and public policies capable of internalizing Pancasila values in a sustainable, innovative, and socially relevant manner to support inclusive and sustainable national integration.